Deferred Prosecution Agreement as an Alternative in Addressing Tax Crimes of the Corporate Taxpayers in Indonesia - Adi Hardiyanto Wicaksono (De Jure: Jurnal Hukum dan Syari'ah, 2022)
Tax revenue from Corporate Taxpayers to the State is very significant, however, this is directly proportional to the large number of crimes committed by Corporate Taxpayers. This is caused by a legal vacuum in terms of postponement or termination of prosecution of Corporate Taxpayers who commit criminal acts in the field of taxation. There are various problems in the criminal justice system in Indonesia related to the prosecutor's authority over the domino effect of crimes committed by corporate taxpayers who should consider strengthening the Deferred Prosecution Agreement (DPA) or Non-Prosecution Agreements (NPA) in cases related to state finances. Based on the normative juridical method with approaches in the form of a positive legal inventory, legal principles, as well as legal systematics and the level of legal synchronization, two conclusions are produced. First, the authority and/or discretion of the DPA against Corporate Taxpayers have not been specifically regulated and is still in the context of terminating criminal investigations in the field of taxation. Second, the Attorney General needs to issue laws and regulations related to DPA for corporations in Indonesia, including Corporate Taxpayers. It is recommended that DPA rules, including procedures, formal requirements, and material requirements, be in the framework of a Government Regulation